Pengaruh Sarana dan Prasarana Perpustakaan terhadap Minat Kunjungan Siswa SMPN 1 Batang Anai - Mustika, Putri; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
Writing this article aims to: (1) determine the existing facilities and infrastructure in the library SMPN 1 Batang Anai and (2) the effect of library facilities and infrastructure to the interest of students visit the library at SMPN 1 Batang Anai. The research method is done through a descriptive study using a quantitative approach. Data was collected through observation by direct observation, whereas for the interview addressed to the head of the library, for the writers questionnaire submitted to 90 students SMP N 1 Batang Anai school year 2014/2015 the study sample. Based on analyzing the data we can conclude (1) infrastructure library of SMP N 1 Batang Anai still inadequate. It can be seen from the vast size of the building is not in accordance with the provisions of the National Library in 1998/1999, as well as the lack of equipment needed; (2) the facilities and infrastructure that exist in the library SMPN 1 Batang Anai greatly affect students' interest, it can be seen from most of the respondents (61.11%) stated that the cause of lazy students visit the library because the library facilities and infrastructure that have not adequate, such as less comfortable library room and stifling. Keywords: Effect, library infrastructure, and interst in the visit